Solutions to the Drawbacks of Photothermal and Photodynamic Cancer Therapy - Deng, Xiangyu; Shao, Zengwu; Zhao, Yanli (Advanced science, 2021)
Phototherapy such as photothermal therapy and photodynamic therapy in cancer treatment has been developed quickly over the past few years for its noninvasive nature and high efficiency. However, there are still many drawbacks in phototherapy that prevent it from clinical applications. Thus, scientists have designed different systems to overcome the issues associated with phototherapy, including enhancing the targeting ability of phototherapy, low‐temperature photothermal therapy, replacing near‐infrared light with other excitation sources, and so on. This article discusses the problems and shortcomings encountered in the development of phototherapy and highlights possible solutions to address them so that phototherapy may become a useful cancer treatment approach in clinical practice. This article aims to give a brief summary about current research advancements in phototherapy research and provides a quick guideline toward future developments in the field. This article discusses the issues and shortcomings encountered in the development of photodynamic and photothermal therapy and highlights possible solutions to address them so that phototherapy may become a useful cancer treatment approach in clinical practice.